Knowledge about Menstruation and Puberty Prior to Menarche and Hygienic Practices during Menstruation Among Adolescent Female College Students in Lahore - RUBINA SARMAD, AFIA ARIF, ASMA SOHAIL, TAJAMMAL MUSTAFA (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the knowledge about menstruation and puberty, and hygiene practices during menstruation among adolescent female college students. Method: A Cross sectional study was conducted among adolescent girls from three colleges in Lahore. Data was collected by interviewing the students using a structured questionnaire after obtaining their consent. SPSS 17.0 was used for data entry and analysis. Results: A total of 332 college girls participated in the study. The age ranged from 15-23 years. Ninety eight percent girls have had their first period at 13-15 years age. Before menstruation began, only 37.7% were aware of it, and the major source of their information was mother (29.6%). Majority of the girls (> 90%) knew about body changes like breast enlargement, appearance of pubic & axillary hair and onset of menstruation as bodily changes during puberty. Whereas, the knowledge about other body changes during puberty was lesser than 70%. Only 32.5% girls reported having received any information on about menstruation by any school teacher. Eighty percent girls said that education about menarche should be imparted in school and 67% thought during 7-8 grades. Majority of girls reported that, at the time of their first period, they did not feel normal or were scared, worried, embarrassed or depressed and only 10% consulted a doctor after their first period. Majority (86.4%) reported their periods as regular. Most of the girls (75%) used disposable sanitary pad, changed pad 2-3 times a day (46.1% ), had privacy in disposing pad (88.6%), and disposed pads in sanitary bag or in garbage (89%). Majority of the girls (88.3%) had not heard about premenstrual symptoms (PMS). Conclusion: The level of knowledge on reproductive health is low in female college students due to lack of basic education and information. Appropriate awareness programs on RH are needed to improve awareness and to clarify misconceptions about reproductive health.